Anxiety and self-care behaviour in patients with chronic systolic heart failure: A multivariate model. (1st February 2018) - Müller-Tasch, Thomas; Löwe, Bernd; Lossnitzer, Nicole; Frankenstein, Lutz; Täger, Tobias; Haass, Markus; Katus, Hugo; Schultz, Jobst-Hendrik; Herzog, Wolfgang
Abstract: Background: While comprehensive evidence exists regarding negative effects of depression on self-care behaviours in patients with chronic heart failure (CHF), the relation between anxiety and self-care behaviours in patients with CHF is not clear. The aim of this study was to analyse the interactions between anxiety, depression and self-care behaviours in patients with CHF. Methods: The self-care behaviour of CHF outpatients was measured using the European Heart Failure Self-care Behaviour Scale (EHFScBS). The Patient Health Questionnaire (PHQ) was used to assess anxiety, the PHQ-9 was used to measure depression severity. Differences between patients with and without anxiety were assessed with the respective tests. Associations between anxiety, self-care and other predictors were analysed using linear regressions. Results: Of the 308 participating patients, 35 (11.4%) fulfilled the PHQ criteria for an anxiety disorder. These patients took antidepressants more frequently (11.8% versus 2.3%, p = .02), had had more contacts with their general practitioner within the last year (11.8 ± 16.1 versus 6.7 ± 8.6, p = .02), and had a higher PHQ-9 depression score (12.9 ± 5.7 versus 6.5 ± 4.7, p < .01) than patients without anxiety disorder. Anxiety and self-care were negatively associated (ß = −0.144, r 2 = 0.021, p = 0.015). The explanation of variance was augmented in a multivariate regression with the predictors age, sex, education, living with a partner, and New York Heart Association (NYHA) class ( r 2 = 0.098) when anxiety was added ( r 2 = 0.112). Depression further increased the explanation of variance (ß = −0.161, r 2 = 0.131, p = 0.019). Conclusions: Anxiety is negatively associated with self-care behaviour in patients with CHF. However, this effect disappears behind the stronger influence of depression on self-care. The consideration of mental comorbidities in patients with CHF is important.